The formation of M101-alike galaxies in the cold dark matter model. Issue 2 (15th September 2021) - Zhang, Dali; Luo, Yu; Kang, Xi; Qu, Han
ABSTRACT: The population of satellite galaxies in a host galaxy is a combination of the cumulative accretion of subhaloes and their associated star formation efficiencies; therefore, the luminosity distribution of satellites provides valuable information of both dark matter properties and star formation physics. Recently, the luminosity function of satellites in nearby Milky Way-mass galaxies has been well measured to satellites as faint as Leo I with MV ∼ −8. In addition to the finding of the diversity in the satellite luminosity functions, it has been noticed that there is a big gap among the magnitude of satellites in some host galaxies, such as M101, where the gap is around 5 in magnitude, noticeably larger than the prediction from the halo abundance matching method. The reason of this gap is still unknown. In this paper, we use a semi-analytical model of galaxy formation, combined with high-resolution N -body simulation, to investigate the probability and origin of such big gap in M101-alike galaxies. We found that, although M101 analogues are very rare with probability of $\sim 0.1\ to\ 0.2\, {{\rm per\, cent}}$ in the local universe, their formation is a natural outcome of the cold dark matter model. The gap in magnitude is mainly due to the mass of the accreted subhaloes, not from the stochastic star formation in them. We also found that the gap is correlated with the total satellite mass and host halo mass. By tracing the formation history of M101-type galaxies, we find that they were likely formed after z ∼ 1 due to the newly accreted bright satellites. The gap is not in a stable state, and it will disappear in 7 Gyr due to mergers of bright satellites with the central galaxy.